Patient‐Derived Upper Tract Urothelial Carcinoma Organoids as a Platform for Drug Screening. Issue 4 (16th December 2021) - Li, Zhichao; Xu, Haibo; Gong, Yanqing; Chen, Wei; Zhan, Yonghao; Yu, Lei; Sun, Yangyang; Li, Aolin; He, Shiming; Guan, Bao; Wu, Yucai; Xiong, Gengyan; et al.
Abstract: Upper tract urothelial carcinomas (UTUCs) are rare entities that are usually diagnosed at advanced stages. Research on UTUC pathobiology and clinical management has been hampered by the lack of models accurately reflecting disease nature and diversity. In this study, a modified organoid culture system is used to generate a library of 25 patient‐derived UTUC organoid lines retaining the histological architectures, marker gene expressions, genomic landscapes, and gene expression profiles of their parental tumors. The study demonstrates that the responses of UTUC organoids to anticancer drugs can be identified and the model supports the exploration of novel treatment strategies. This work proposes a modified protocol for generating patient‐derived UTUC organoid lines that may help elucidate UTUC pathophysiology and assess the responses of these diseases to various drug therapies in personalized medicine. Abstract : The lack of models accurately reflecting disease nature and diversity of upper tract urothelial carcinoma (UTUC) impedes the research on its pathobiology and clinical management. This study demonstrates an organoid culture system to generate UTUC organoids from clinical samples. These organoid models retain the characteristics of their parental tumors and support the exploration of novel treatment strategies.